De symboliek van het snuffelen. Hoe een luchtverontreinigingsmonitor uitgroeide tot nationaal symbool - Maas, Ad; Buijsman, Ed (Studium, 2014)
Recently, the Dutch national museum for the history of science and medicine, Museum Boerhaave in Leiden, acquired four air pollution monitors for its collection. These instruments were part of the Dutch national network for the measurement of air pollution, established in the 1970s. The monitors mark the transition in analytical chemistry from traditional wet-chemical techniques to the use of electronic and automatic tools. The significance of these instruments is not only scientific: they also played a social role. In the 1970s and 1980s, these air pollution monitors (popularly known as snuffelpalen (‘sniffer poles’) became a symbol for environmental worries and distrust with the political establishment, a trend we now consider as typical of that era.